PENGARUH GAYA KEPEMIMPINAN, DISIPLIN KERJA DAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA DINAS PERDAGANGAN DAN PERINDUSTRIAN KABUPATEN GOWA - Nur Fatma; Ifah Finatry Latiep; Reni Furwanti (Program Studi Manajemen Fakultas Ekonomi Universitas Balikpapan, 2020)
This study aims to determine the effect of leadership style, work discipline and motivation on the performance of employees at the Trade and Industry Service of Gowa Regency. This type of research is quantitative research that is to find out and analyze the influence of leadership style, work discipline and motivation on the performance of the District Trade and Industry Office. The results of this study found that leadership style has a positive and not significant effect on performance, work discipline has a positive and significant effect on employee performance, motivation has a positive and not significant effect on employee performance. Work motivation has the most dominant influence positively and significantly on the performance of employees of the Trade and Industry Office of Gowa Regency.